2019
DOI: 10.1364/ol.44.003909
|View full text |Cite
|
Sign up to set email alerts
|

CEP-stable high-energy ytterbium-doped fiber amplifier

Abstract: We report on the CEP stabilization of an Yb-doped fiber amplifier system delivering 30 µJ, 100 fs pulses at 100 kHz repetition rate. A single shot, every shot, measurement of the CEP stability based on a simple f-2f interferometer is performed, yielding a CEP standard deviation of 320 mrad rms over 1 s. Long-term stability is also assessed, with 380 mrad measured over one hour. This level of performance is allowed by a hybrid architecture including a passively CEP-stabilized front-end based on difference frequ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…For example, Lavenu et al combined compression in MPC and compression in a large diameter core capillary, to demonstrate the generation of 6.8 fs, 140 µJ pulses at 150 kHz repetition rate (21 W average power) from a commercial Yb-fiber CPA [108]. By replacing the front-end of the CPA by a system based on difference frequency generation (DFG), the same group demonstrated that the nonlinearly compressed pulses from the CPA can be CEP stabilized [109].…”
Section: Post-compression Of High Power Cpasmentioning
confidence: 99%
“…For example, Lavenu et al combined compression in MPC and compression in a large diameter core capillary, to demonstrate the generation of 6.8 fs, 140 µJ pulses at 150 kHz repetition rate (21 W average power) from a commercial Yb-fiber CPA [108]. By replacing the front-end of the CPA by a system based on difference frequency generation (DFG), the same group demonstrated that the nonlinearly compressed pulses from the CPA can be CEP stabilized [109].…”
Section: Post-compression Of High Power Cpasmentioning
confidence: 99%
“…In this case, a simpler laser technology, with very high gain materials, can be turned efficiently into a femtosecond source. Finally, a temporal compression setup based on a bulk nonlinear MPC was used in a carrier‐envelope phase stabilized system, [ 66 ] demonstrating the compatibility of both techniques despite the long beam path inside the cell.…”
Section: Experimental Implementations Of Temporal Compression In Mpcsmentioning
confidence: 99%
“…We make this distinction because temporal characterization is a demonstration of the attosecond pump-probe capability. As shown in Figure 1, single-pass HHG can provide high harmonics [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] up to tens of nJ per shot at 1 MHz by using powerful driving lasers with an average power up to ~100 W [37][38][39][40][41][42][43] and the attosecond pulses [44][45][46][47][48][49][50][51][52][53][54][55] up to hundreds of pJ per shot at 100 kHz. Intracavity HHG can deliver the high harmonics with the repetition rates up to hundreds of MHz [56][57][58][59][60][61][62][63].…”
Section: Introductionmentioning
confidence: 99%